Enterprise Systems And Resource Planning To Assit Msmes - Rizki Alfadillah Nasution; Elvira Iskandar (Pusat Riset dan Inovasi Nasional, 2023)
This service is about system utilization (enterprise resource planning) in micro, small and medium enterprises (MSMEs) in Indonesia. Applying enterprise resource planning to MSMES can help increase flexibility and integrate entire business processes, such as inventory management, finance, production, and sales. However, the implementation of enterprise resource planning requires mature preparation, including proper selection of suppliers, optimization of internal teams, and preparation of human resources. The research methodology used is a participatory action learning system with the active participation of MSMES stakeholders and enterprise resource planning providers. The implementation process of the ENERPRISE Resource Planning system in MSMES includes the phases of meetings, planning, system design, training, and support, as well as the use of the system in business operations. The implementation steps of the Enterprise Resource Planning system in MSMES include business information documents, functional requirements documents, user acceptance testing, training, and go-live.